Simultaneous Vt selection and assignment for leakage optimization. - Khandelwal, V.
This paper presents a novel approach for leakage optimization through simultaneous Vt selection and assignment. Vt selection implies deciding the right value for Vt and assignment implies deciding which gates should be assigned a particular threshold voltage. We also include the effect of variability in threshold voltage on delay and leakage due to fabrication process variations in our formulations and present a scheme that lets the designer control the leakage and delay variability in his design. The proposed algorithm is a general mathematical formulation that has been shown to trivially extend to multiple threshold voltages.
Keywords: Delay variability; Fabrication process variations; General mathematical formulation; Leakage optimization; Multiple threshold voltages; Vt assignment; Vt selection